The Mother, the Son and the Madness: Shared Experiences of a Chronic Illness in Niamey (Niger) - Aït Mehdi, Gina (Swiss Journal of Sociocultural Anthropology, 2018)
Khadija lives with her son, whose unpredictable mental disorders have brought profound, existential uncertainty into the life of this Nigerien family. With such chaotic circumstances confronting her, the mother puts great effort into recreating stability out of these turmoils, while not abandoning the hope for their disappearance of the latter. Beyond the practical and narrative (re)positioning of filial relationships reveals in Khadija’s accounts of her son’s illness, this article analyses how her endeavours keep the family together.